Calcium Metabolism Disorder in Paediatric Age Group and its Homeopathic Management - Patil, D. B.; Malokar, K.; Raut, M.; Golekar, B. N.; Rathod, L. D.; Chauhan, S. (Homœopathic Links, 2013)
Calcium metabolism disorder in children may lead to an excess or deficiency of calcium in blood – respectively, hypercalcaemia and hypocalcaemia. There are various causes that lead to calcium metabolism disorder. This work is an effort towards the diagnosis and early treatment and prevention of its recurrence with constitutional remedies and thus highlighting the effectiveness of homeopathy in the management of childhood calcium metabolism disorder.
Keywords: Calcium; Hypercalcaemia; Hypocalcaemia